2019
DOI: 10.1016/j.rama.2019.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Soil Fauna Accelerate Dung Pat Decomposition and Nutrient Cycling into Grassland Soil

Abstract: Soil fauna play critical roles in various ecosystem functions and services, but empirical data measuring their impact on dung pat decomposition and subsequent nutrient cycling into rangeland soils are limited. The objective of this study was to quantify the effect of soil fauna, using dung beetle as an indicator, on dung decomposition and subsequent translocation of dung nutrients into grassland soil over time. A field experiment was conducted early in the summer season and late in the summer season of 2014 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 33 publications
0
18
0
1
Order By: Relevance
“…There has been great interest in the role dung beetles may play in nutrient cycling in soils but particularly the impact they may have in agroecosystems. For example, in sandy loam soils, dung beetles have been found to increase the nutrient content of pasture soils 2-10 cm below the surface [29], resulting in the increased mineralization of organic nitrogen [8,30] and the transfer of available phosphorus, nitrogen, and exchangeable potassium by paracoprid beetles [31]. This study and Yamada et al both used species in the genus Onthophagus to assess how dung beetle activity facilitates the transfer of nutrients into soils.…”
Section: Discussionmentioning
confidence: 99%
“…There has been great interest in the role dung beetles may play in nutrient cycling in soils but particularly the impact they may have in agroecosystems. For example, in sandy loam soils, dung beetles have been found to increase the nutrient content of pasture soils 2-10 cm below the surface [29], resulting in the increased mineralization of organic nitrogen [8,30] and the transfer of available phosphorus, nitrogen, and exchangeable potassium by paracoprid beetles [31]. This study and Yamada et al both used species in the genus Onthophagus to assess how dung beetle activity facilitates the transfer of nutrients into soils.…”
Section: Discussionmentioning
confidence: 99%
“…Soils are sandy to fine sandy loam texture. Soil organic matter content ranged between 14 and 33 mg/g at the 0- to 10-cm depth and between 4 and 9 mg/g at the 10- to 20-cm depth ( Evans et al, 2019b ). Meadows are seasonally wet in early to late spring due to the rising water table.…”
Section: Methodsmentioning
confidence: 99%
“…A number of studies have reported that dung beetles can play important roles in nutrient cycling, greenhouse gas mitigation, parasite suppression, and overall trophic regulation ( Bang et al 2005 , Yamada et al 2007 , Nichols et al 2008 , PenttilĂ€ et al 2013 , Santos-Heredia et al 2018 , Evans et al, 2019a ). In addition, dung beetle activity can increase soil nutrients at the soil surface by incorporating nutrients from the dung into the soil ( Evans et al 2019b ). Therefore, dung beetle activity is recognized as being very important for ranch management by promoting and maintaining healthy cattle-grazed rangeland ecosystems ( Aarons et al 2009 , MenĂ©ndez et al 2016 ).…”
mentioning
confidence: 99%
“…The published data on the effects of dung beetle activity on soil carbon levels (for example, Menendez, Webb and Orwin, 2016;Evans et al, 2019) have primarily concerned endocoprid species (which do not bury dung, Photo 25) or shallow-tunnelling species, and indicate that such species transfer only small amounts of the dung carbon into the soil (often as dissolved organic carbon (DOC)) and do little to increase persistent carbon stores in soil (Menendez, Webb and Orwin, 2016;Evans et al, 2019). In marked contrast, deep-tunnelling dung beetles bury substantial amounts of dung (Edwards and Aschenborn, 1987;Doube, 1991) but, apart from Bubas bison, none has had its capacity to increase SOC levels assessed quantitatively.…”
Section: Impact On Soil Organic Carbon Stocksmentioning
confidence: 99%